2005
DOI: 10.1074/jbc.m413134200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Key Profibrotic Mechanisms in Transgenic Fibroblasts Expressing Kinase-deficient Type II Transforming Growth Factor-β Receptor (TβRIIΔk)

Abstract: We have generated transgenic mice expressing a kinase-deficient type II transforming growth factor-␤ (TGF␤) receptor selectively on fibroblasts (T␤RII⌬k-fib). These mice develop dermal and pulmonary fibrosis. In the present study we explore activation of TGF␤ signaling pathways in this strain and examine the profibrotic properties of explanted transgenic fibroblasts including myofibroblast differentiation and abnormal metalloproteinase production. Gene expression profiles of littermate wild type or transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 47 publications
4
47
0
1
Order By: Relevance
“…Dermal dcSSc fibroblasts overexpress an array of proadhesive and procontractile proteins (23), including CCN2, which is also known as connective tissue growth factor (4,21,24,25). To assess whether endogenous TGF␤ signaling through the type I TGF␤ receptor is involved in the overexpression of profibrotic genes by dcSSc fibroblasts, we incubated dermal fibroblasts derived from healthy controls and from lesional areas of the skin of dcSSc patients for 24 hours with SD208, an ALK-5/TGF␤RI kinase inhibitor (19,20). Cell extracts were then prepared, and subjected to SDS-PAGE and (25 g) from dermal fibroblasts derived from normal subjects and from lesional areas of the skin of patients with dcSSc were subjected to Western blot analysis with antimoesin, antivinculin, anti-CCN2, antiezrin, anti-␣-smooth muscle actin (anti-␣-SMA), anti-␣4 integrin, anti-␤1 integrin, and anti-GAPDH antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dermal dcSSc fibroblasts overexpress an array of proadhesive and procontractile proteins (23), including CCN2, which is also known as connective tissue growth factor (4,21,24,25). To assess whether endogenous TGF␤ signaling through the type I TGF␤ receptor is involved in the overexpression of profibrotic genes by dcSSc fibroblasts, we incubated dermal fibroblasts derived from healthy controls and from lesional areas of the skin of dcSSc patients for 24 hours with SD208, an ALK-5/TGF␤RI kinase inhibitor (19,20). Cell extracts were then prepared, and subjected to SDS-PAGE and (25 g) from dermal fibroblasts derived from normal subjects and from lesional areas of the skin of patients with dcSSc were subjected to Western blot analysis with antimoesin, antivinculin, anti-CCN2, antiezrin, anti-␣-smooth muscle actin (anti-␣-SMA), anti-␣4 integrin, anti-␤1 integrin, and anti-GAPDH antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts from patients with dcSSc overexpress a series of profibrotic proteins. In this study, we investigated the ability of SD208, a TGF␤RI kinase (ALK-5) inhibitor (19,20), to prevent the overexpression of profibrotic proteins by dermal fibroblasts from patients with earlyonset dcSSc, as well as the ability of dermal fibroblasts from patients with early-onset dcSSc to excessively adhere to and contract ECM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a large body of indirect evidence implicating the overexpression of TGF␤ ligand or receptor in the pathogenesis of SSc (23), and several recent studies have demonstrated that blocking TGF␤ ligand may abrogate fibrosis in a number of mouse models (24). In addition, activation of TGF␤ signaling pathways constitutively in fibroblasts replicates many of the key histologic and biochemical features of established SSc (25). In this context, it is disappointing that our study did not show any evidence of efficacy for .…”
Section: Discussionmentioning
confidence: 99%